Risk of Acquiring Vibrio parahaemolyticus in Water and Shrimp from an Aquaculture Farm - Chai, Fung Pui; Lesley Maurice, Bilung; Nur Bainun, Mohd Zin; Nurulhuda Najihah, Zainal Abidin; Vincent, Micky; Kasing, Apun (Graduate School of Kuroshio Science, Kochi University, 2014)
Vibrio parahaemolyticus is an important foodborne pathogen causing significant economic problems within the aquaculture industry worldwide. This study was conducted to determine the occurrence and concentration of V. parahaemolyticus in water and shrimp from aquaculture farms. The relationship between the concentration of V. parahaemolyticus in ponds and environmental parameters was also studied. A total of 264 water samples and 27 shrimp samples from a selected aquaculture farm were examined using the most probable number-polymerase chain reaction (MPN-PCR) method, a method that incorporates both the count and detection of toxR gene. The correlation between the concentration of V. parahaemolyticus in both types of the samples and environmental parameters (temperature, pH and salinity) was analyzed statistically by the paired T-test. Based on the results, 132 water samples (50%) and 11 shrimp samples (41%) were toxR positive. The concentration of V. parahaemolyticus in all the water and shrimp samples using MPN method was found to be more than 1,100 MPN/g. The environmental parameters examined were not significantly correlated with the concentration of V. parahaemolyticus in both types of samples. The results concluded that there was occurrence of V. parahaemolyticus in the aquaculture farm. Therefore, this study highlighted the potential risk of infection by V. parahaemolyticus from an aquaculture farm to humans. The findings obtained from this study could act as baseline data for the risk assessment of V. parahaemolyticus in water and shrimp samples from aquaculture farms. This will further provide useful surveillance data for relevant authorities.